Advances in human factors in sports, injury prevention and outdoor recreation : proceedings of the AHFE 2017 International Conference on Human Factors in Sports, Injury Prevention and Outdoor Recreation, July 17-21, 2017, the Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Human Factors in Sports, Injury Prevention and Outdoor Recreation, July 17-21, 2017, the Westin Bonaventure Hotel, Los Angeles, California, USA. (2018) - Unknown
No abstract available